RELIGIOUS HUMANISM IN EDUCATION: ANALYSIS OF QUR’ANIC VERSES ON HUMANITY - Hamid, Asep Lukman; Drajat, Manpan; Enjang, Enjang (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The Quran strongly emphasizes humanity. Unpacking this message demands critical study to foster human potential in line with its core essence. This study analyzes the humanist values present in the Quran and their implementation in education. Employing a qualitative, descriptive analysis, this library research uses the Quran as its primary source. The study aims to identify the human values in the Quran and examine their application in educational settings. Results indicate that Quranic discussions on humanity revolve around humans as caliphs entrusted with responsibility. Fulfilling these responsibilities rests on the Aqidah of monotheism and the Quran. Quranic religious humanism is constructed through principles of purposeful freedom, equality, brotherhood, and tolerance. In education, teachers should prioritize a humanist approach to nurture students’ potential, cultivating a supportive, interactive, liberating, and democratic learning climate. This study recommends that Islamic education incorporate religious humanist values into the curriculum and classroom practices.